Fabrication of a new PVDF/SbSI nanowire composite for smart wearable textile. (10th October 2019) - Jesionek, Marcin; Toroń, Bartłomiej; Szperlich, Piotr; Biniaś, Włodzimierz; Biniaś, Dorota; Rabiej, Stanisław; Starczewska, Anna; Nowak, Marian; Kępińska, Mirosława; Dec, Jan
Abstract: In this paper, a new fabrication method for Polyvinylidene fluoride/SbSI nanowire composite is presented. Polyvinylidene fluoride (PVDF) is a specialist thermoplastic fluoropolymer with very good mechanical, chemical and thermal properties. Additionally, PVDF shows piezoelectric, pyroelectric, and ferroelectric properties. Antimony sulfoiodide (SbSI) nanowires (lateral dimensions of 10 nm–100 nm and lengths up to a few micrometres) are also piezoelectric compound with one of the best electromechanical and piezoelectric coefficient (k33  = 0.9 and dV  = 0.9 × 10 −9  C/N). SbSI nanowires have been added to improve piezoelectric properties of PVDF. The prepared SbSI nanowires were bound with PVDF in a mass ratio of 15:85, which was the fibre formation input with the addition of SbSI nanowires at different take-up velocities. An active layer of nanogenerator was prepared from the fabricated PVDF/SbSI nanowire composite. The preliminary investigations of compression and vibrations, allowed for the determination of the composites open circuit voltage 1.2 Vp-p and 2.5 Vp-p, respectively. Generated powers under impact have reached values PS  = 408.8(52) μW/cm 2 and PV  = 3.464(53) mW/cm 3, respectively. Graphical abstract: Image 1086258 Highlights: The new fabrication method for PVDF/SbSI nanowire composite with nanowires aligned along PVDF fibres. The use of PVDF/SbSI nanowire composite for the construction of nanogenerators and piezoelectric textile. Physical properties, chemical composition and morphology of PVDF/SbSI nanowire composite.